ANALISIS PENGGUNAAN MEDIA AUDIO VISUAL PADA STUDI ILMU PENGETAHUAN SOSIAL UNTUK MENINGKATKAN HASIL STUDI SISWA DI KELAS IV SEKOLAH DASAR - Sabrina, Adzkia; Ridwan, Ita Rustiati; Susilawati, Susilawati (Didaktika, 2021)
Social studies are studied in elementary school. The main objective of social studies is to allow students to become knowledgeable, thinking, and involved citizens in the local and the world community. But in fact, shows that the learning result doesn’t meet the purpose. The primary basis for teaching social studies is depending on the literature as a single-source guide by teachers as a center has become common. This classic method makes students have difficulties in learning and understanding. Applying audio-visual media can help students to be successful in learning IPS, it affirmed by prior researchers. This study's purpose is to analyze: enhancing student achievement in social studies through audio-visual media in grade fourth of elementary school A systematic review represents the research process in qualitative studies. Data were collected from various articles of the researcher. Milles and Huberman’s techniques are the main method used for data analysis. They divided the process of analysis into three phases, consisting of data reduction, data displays, and diagnosis. Based on the analysis of research data collection showed that audio-visual media usage improving students' achievement of social studies in a grade fourth elementary school. Studying social studies through audio-visual media has been proven to make students more creative, motivated, and easy to follow the teacher's explanations during learning activities